T cell subsets in human airways prior to and following endobronchial administration of endotoxin. Issue 4 (25th February 2015) - Ronit, Andreas; Plovsing, Ronni R.; Gaardbo, Julie C.; Berg, Ronan M.G.; Hartling, Hans J.; Konge, Lars; Iversen, Martin; Ullum, Henrik; Møller, Kirsten; Nielsen, Susanne Dam
Abstract Background and objectives Bronchial instillation of lipopolysaccharide (LPS) provides a reversible model of lung inflammation that may resemble early stages of acute respiratory distress syndrome (ARDS). We investigated the distributions of T‐cell subsets in the human airways and sought to determine whether pro‐ and anti‐inflammatory T cells are involved in the local immune response to lung inflammation. Methods Bronchoalveolar lavage (BAL) was performed in 15 healthy volunteers, after which Escherichia coli LPS (4 ng/kg) was administered. BAL was repeated at 2, 4, 6, 8 or 24 h after instillation of LPS. Results BALF CD4+ and CD8+ T cells were characterized by expression of activation markers (HLA‐DR+CD38+), the proportion of cells expressing naïve markers (CD45RA+CD27+CCR7+) was lower, and that of cells expressing effector memory markers (CD45RA‐CD27+CCR7‐) was higher, compared with peripheral blood. Bronchial LPS induced a local inflammatory response with recruitment of CD4+ (P = 0.014), CD8+ T cells (P = 0.034), an increase in the proportion of CD4+CD25+CD127lowFoxp3+ regulatory T cells (Tregs) (P = 0.045) and a tendency towards an increase in CD4+CD161+ cells (P = 0.071) were observed. Conclusions A unique distribution of T cells with little day‐to‐day variation was found in human airways. An increase in Tregs after endobronchial LPS suggests a role for Tregs during early stages of pulmonary inflammation.